A new type of flexible energy harvesting device working with micro water droplets achieving high output. Issue 41 (14th October 2021) - Gao, Dan; Liu, Changhong; Fan, Shoushan
Abstract : When a drop of tap water was added onto the hybrid device, the parts of Al–air battery and hydrocapacitor would start working successively using the tap water as electrolyte. Abstract : Aluminum is one of the most promising candidates for metal–air batteries due to its abundance, high specific energy and theoretical voltage. However, the Al–air battery is hindered by a high corrosion rate in an aqueous alkaline solution. In this work, a new type of hybrid device is presented, which combines sandwich-like hydrocapacitor and Al–air battery together using a common polyaniline composite/carbon nanotube (PANI/CNT) electrode. This device works under an all-solid-state condition without adding the electrolyte in advance, which could reduce corrosion greatly, control the initiation and cessation of reactions, and prevent harmful leakage or deformation of the electrolyte completely when it is not used. It could provide a maximum open-circuit voltage of 1.5 V within one minute after adding only a drop of tap water instead of using alkaline and saline electrolyte and maintain over 1 V for more than 3 hours. When another drop of tap water was added, it could start working again. Moreover, daily measurements of the open-circuit voltage of the same device were tested repeatedly for a month and the maximum 1 V could be maintained, which shows circularity and stability. In addition, the integration of the device was also demonstrated using three devices to light up a light-emitting-diode. The performance could still maintain at a high level under bending conditions. The working mechanism is also discussed in this work.